2022
DOI: 10.1001/jamanetworkopen.2022.8212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Interdisciplinary Weight Loss and Lifestyle Intervention on Obstructive Sleep Apnea Severity

Abstract: IMPORTANCEObesity is the leading cause of obstructive sleep apnea (OSA); however, the effects of weight loss and lifestyle interventions on OSA and comorbidities remain uncertain. OBJECTIVE To evaluate the effect of an interdisciplinary weight loss and lifestyle intervention on OSA and comorbidities among adults with moderate to severe OSA and overweight or obesity. DESIGN, SETTING, AND PARTICIPANTS The Interdisciplinary Weight Loss and Lifestyle Intervention for OSA (INTERAPNEA) study was a parallel-group ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 63 publications
3
25
0
Order By: Relevance
“…Fortunately, pharmacological interventions such as glucagon-like peptide-1 receptor agonists (GLP-1RA) that treat the obesity-diabetes-OSA triad can make substantial inroads in reversing the trends in morbidity and cost associated with obesity-related illnesses. Indeed, recent studies showed that weight loss via lifestyle modifications and pharmacotherapy can lead to resolution of OSA [ 34 , 35 ]. For example, a randomized controlled trial (RCT) intervention of lifestyle and other interventions that led to weight loss was associated with discontinuation of continuous positive airway pressure therapy in 62% of OSA patients at the 6-month follow-up [ 34 , 36 ].…”
Section: Epidemiology Of Obstructive Sleep Apnea Obesity and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, pharmacological interventions such as glucagon-like peptide-1 receptor agonists (GLP-1RA) that treat the obesity-diabetes-OSA triad can make substantial inroads in reversing the trends in morbidity and cost associated with obesity-related illnesses. Indeed, recent studies showed that weight loss via lifestyle modifications and pharmacotherapy can lead to resolution of OSA [ 34 , 35 ]. For example, a randomized controlled trial (RCT) intervention of lifestyle and other interventions that led to weight loss was associated with discontinuation of continuous positive airway pressure therapy in 62% of OSA patients at the 6-month follow-up [ 34 , 36 ].…”
Section: Epidemiology Of Obstructive Sleep Apnea Obesity and Diabetesmentioning
confidence: 99%
“…Indeed, recent studies showed that weight loss via lifestyle modifications and pharmacotherapy can lead to resolution of OSA [ 34 , 35 ]. For example, a randomized controlled trial (RCT) intervention of lifestyle and other interventions that led to weight loss was associated with discontinuation of continuous positive airway pressure therapy in 62% of OSA patients at the 6-month follow-up [ 34 , 36 ].…”
Section: Epidemiology Of Obstructive Sleep Apnea Obesity and Diabetesmentioning
confidence: 99%
“…Potential participants were men aged 18-65 years with CPAP-treated moderate-to-severe OSA (i.e., AHI equal or greater than 15 events per hour of sleep) and a body mass index (BMI) equal to or greater than 25 kg/m 2 . The sole inclusion of men in our sample was not only based on the higher incidence and prevalence of OSA in this population [1], but also on the well-evidenced differences between men and women in OSA phenotypes [38] and the effectiveness of weight loss interventions [20,37,[39][40][41]. Exclusion criteria included present participation in a weight loss program, presence of any psychological/psychiatric disorder, and/or any other primary sleep disorder which was not secondary to OSA.…”
Section: Participantsmentioning
confidence: 99%
“…This study included two groups: a usual-care/control group, which received CPAP as the standard care of OSA, and a weight loss and lifestyle intervention group, which received an eight-week interdisciplinary intervention, including nutritional behavior change, aerobic exercise, sleep hygiene, and alcohol and tobacco cessation, combined with usual-care. Changes in OSA severity and body weight at 6 months after intervention indicated that participants in the intervention group reduced a significantly greater amount of their initial AHI and body weight (57% and 7%, respectively) than those in the usual-care/control group (2% and 1%) [20]. INTERAPNEA provides an opportunity to examine the effects of a behavior-induced weight loss intervention on dietary behavior and diet quality in men with moderate-to-severe OSA who received, among other intervention components, nutritional education and behavior change.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation